Cosmetic gynecology: An emerging subspecialty of obstetrics and gynecology - Manvi Verma (MGM Journal of Medical Sciences, 2023)
Cosmetic gynecology is the upcoming super specialty of obstetrics and gynecology that has gained momentum over the last decade globally. These procedures differ from other aesthetic surgical procedures as they focus on the functional enhancement of female sexuality apart from the aesthetic improvement of genitalia. However, many controversies exist in the cosmetic gynecology domain regarding its applications, morality, need, etc. It is the need of the hour to encourage the practice and skill-based learning in this specialty across the academic institutions on the scientific path so that unspoken and unmet needs of women are addressed at the local level, thereby overcoming the present challenges of affordability and lack of awareness. This review article aimed to briefly describe the scope and latest developments in the field of cosmetic gynecology.